Emotion Goals: What Do Sexual Offenders Want to Feel? - Garofalo, Carlo (Int J Offender Ther Comp Criminol, 2019)
Sexual offenders typically experience more negative emotions and greater difficulties in regulating emotions than non-offenders. However, limited data exist on what sexual offenders want to feel (i.e., their emotion goals). Notably, emotion goals play a key role in emotion regulation and contribute to emotional experience. The present study tested whether sexual offenders (N = 31) reported higher scores for negative emotion goals and lower scores for positive emotion goals, compared with general offenders (N = 26) and non-offenders (N = 26). In addition, we tested whether sexual offenders differed from the other two groups in their perceived pleasantness and perceived utility of emotions. Sexual offenders reported greater scores for the emotion goal of sadness, and lower scores for the emotion goal of excitement, compared with both general offenders and non-offenders. State and trait levels of these emotions could not fully account for these differences. Furthermore, sexual offenders reported lower perceived pleasantness for sadness than general offenders and lower perceived pleasantness for excitement compared with both other groups. Finally, sexual offenders reported greater perceived utility of sadness than non-offenders. These novel findings and their implications for research and interventions are discussed in the context of sexual offenders’ emotional dysfunction.